DESIGN OF AN IOT-BASED SOLAR PHOTOVOLTAIC IRRIGATION PUMPING SYSTEM FOR RAINFED FARMING IN KEMBANG SARI VILLAGE - Wayan Pasek Resti Awan; Fabiano Yanel Ayawaila; I Gede Para Atmaja; Johan Makal; Siti Maisaroh (EDUCATIONE, 2026)
Rainfed agriculture is highly vulnerable to rainfall variability and limited irrigation infrastructure, resulting in unstable agricultural production, particularly during prolonged dry periods. This study aimed to develop a detailed engineering design for an integrated solar-powered irrigation system equipped with Internet of Things monitoring for rainfed farmland in Kembang Sari Village. The study employed a research-and-development approach focusing on electrical-load analysis, photovoltaic and battery sizing, pump and reservoir configuration, hydraulic-system design, and sensor-based monitoring architecture. The proposed system integrates photovoltaic modules, a solar charge controller, lithium iron phosphate batteries, an inverter, a 1.5-hp irrigation pump, a water reservoir, and sensors for soil moisture, water level, flow rate, battery condition, and pump status. The results showed a total connected load of 1,156 W and a daily energy requirement of approximately 6,019 Wh. Considering an overall system efficiency of 80% and five peak-sun hours per day, the required generation capacity was estimated at 7,523.75 Wh/day. The recommended configuration consists of seven 250-Wp photovoltaic modules with a total capacity of 1.75 kWp, a minimum 50-A charge controller, a 6-kW inverter, and two 48-V 100-Ah lithium iron phosphate batteries. The hydraulic subsystem uses a pump with an estimated 12-m head and a 36-m³ reservoir to support a target water supply of approximately 36 m³/day. The integrated monitoring system enables remote supervision, automatic protection, and data-informed irrigation management. The design provides a technically coherent basis for prototype construction, although field validation is required to assess actual solar generation, pump performance, water adequacy, sensor reliability, maintenance requirements, and economic feasibility.